Good news from Africa : community transformation through the church - Woolnough, Brian E. (Regnum resources for mission., 2013)
This book discusses how sustainable, holistic community development can be, and is being, achieved through the work of the local church. Leading African development practitioners describe different aspects of development through their own experience.